HUBUNGAN PROTEIN URINE DAN MEAN ARTERI PRESSURE DENGAN KEJADIAN HIPERTENSI PADA IBU HAMIL TRIMESTER III DI RSU PRIMA HUSADA SIDOARJO - Nur Masruroh; Andreas Putro Ragil Santoso (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2020)
Preeclampsia is still a major health problem for pregnant women in the world and in Indonesia. These are the three main causes of maternal death. Preeclampsia is a complication in pregnancy characterized by hypertension, protein in the urine and edema in the extremities. This study aims to determine the relationship between urine protein levels and mean arterial pressure in third trimester pregnant women at Prima Husada Hospital Sidoarjo. This research method is cross sectional analytic observation with a sample size of 30 pregnant women. Urine protein levels are obtained by examining using the urine dipstick method. Meanwhile, mean arterial pressure is obtained by measuring the mother's blood pressure and then calculated using a formula to determine the results. Data analysis using Chi Square. Results: Of the 30 respondents, 20% were positive on the examination of protein levels and 30% were positive on the examination of the mean arterial pressure. On examination of urine protein with hypertension, the result was p = 0.272 (> 0.005). The results of the analysis of the relationship between MAP and hypertension obtained p = 0.001 (<0.005). Conclusion: There is no relationship between protein levels and hypertension and there is a relationship between mean arterial pressure and hypertension. It is expected that pregnant women carry out routine pregnancy checks at least 4 times during pregnancy and midwives routinely carry out early detection of preeclampsia to prevent complications in the mother and the fetus.